Evaluasi K3 pada Proyek Gedung BNN Bandung dengan Metode HIRARC - Ganjar Jojon Johari; Reinatha Aprilia (Jurnal Konstruksi, 2026)
The construction project of the BNN Bandung City Office Building involves high-risk activities such as superstructure works, mechanical–electrical–plumbing (MEP) installations, and wastewater treatment plant (IPAL) installations. These activities have the potential to cause occupational accidents if proper control measures are not implemented. This study aims to identify Occupational Health and Safety (OHS/K3) hazards based on Job Safety Analysis (JSA) documents and to analyze risk levels using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The research method utilizes secondary data in the form of project JSA documents, which are analyzed through the stages of hazard identification, risk assessment, and control recommendations. Risk levels are determined by multiplying likelihood and severity values and are then classified into low, medium, and high categories in accordance with HIRARC standards. The results show that the identified hazards include falls from height, being struck by materials, slips, electrical hazards, chemical exposure, and confined space risks. Most risks fall into the medium to high categories. In superstructure works, high risk mainly arises from working at height. In MEP works, dominant risks are related to electrical hazards. Meanwhile, in IPAL works, high risk is identified in confined spaces with potential gas exposure. In conclusion, the majority of hazards in this project are categorized as medium to high risk, indicating that risk control efforts should be focused on superstructure, MEP, and IPAL activities in accordance with applicable OHS regulations.